Practice Overview Care and Health Standards - Musta’in, Musta’in; Marni, Marni; Yuniarti, Tri; Ramdhani, Ailza; Sani, Fakhrudin Nasrul (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stunting, a condition of chronic malnutrition, impairs the physical and cognitive development of toddlers. This condition is often influenced by maternal health during pregnancy, inadequate nutrition, and recurrent illnesses in children. Despite improvements, Karanganyar Regency remains one of the regions in Central Java with high stunting prevalence, necessitating effective prevention strategies.Objective: This study aims to explore family roles and parenting practices in addressing stunting in toddlers in Gebyog Village, Mojogedang District. Methods: A qualitative phenomenological approach was employed using purposive sampling of 10 households with stunted children in Gebyog Village. Data collection involved in-depth interviews and field notes conducted in October-November 2024. Analysis followed the Colaizzi method to explore parental experiences, perspectives, and practices related to stunting prevention.Results: Most parents (70%) practice appropriate parenting aligned with health standards, such as providing exclusive breastfeeding, balanced complementary feeding, maintaining a clean environment, ensuring proper sanitation, participating in health education, and engaging in integrated health service posts. However, 30% of parents demonstrated inadequate care practices due to limited knowledge and resources. Conclusion: Strengthening parental education and support systems is crucial for improving parenting practices and reducing stunting prevalence. Integrated efforts involving health professionals and community initiatives are essential to ensure sustainable impact.